A manuscript vocabulary of Bangala by Luke Tunnard - Tunnard (†1926), Luke; Nakao , Shuichiro (AAeO - Afrikanistik-Aegyptologie-Online, 2024)
This work is a vocabulary of Bangala, a Bobangi-based pidgin and historically a sister to Lingala, as spoken in the southwestern South Sudan (and the northeastern Democratic Republic of Congo) around the end of the 19th century and the early 20th century. This original vocabulary, handwritten on a copy of Madan (1905) now kept at Makerere University Library (Kampala, Uganda) was collected by Major Luke Tunnard (†1926), a British soldier who was appointed to serve in colonial South Sudan during the First World War, but has left unpublished for a century. This vocabulary, however, is a largest vocabulary of Bangala as recorded on the South Sudanese side, and as such represents an important contribution to the study of this hitherto less studied pidgin.